Where the fields have no name: urban-rural transitions in the Lisbon Region planning history - Marat-Mendes, T.; Borges, J. C.; Lopes, S.; Pereira, M. (CIDADES, Comunidades e Territórios, 2020)
This paper discusses the existing urban-rural dichotomy in Portuguese urban planning, assuming its importance on food-provision, a basic human need. Our analysis stems from an historical overview at two scales, regional and municipal, within the Lisbon Region. Specifically, we identify key changes between two time-periods: the midtwentieth century, when design-based planning was established in Portugal for larger settlements, and nowadays, when it covers the totality of the national territory, based on land-use. We review these strategies, assessing what approaches would best encompass a sustainable transition of the food system. We start with the scheme of regional radial axis by architect Étienne de Gröer in contrast with the 2002 Lisbon Regional Plan. We furthermore expose two urbanization plans from 1940s: that of Vila Franca de Xira (1946) by Miguel Jacobetty and Faria da Costa and that of Palmela (1948) by João António Aguiar. Such plans, highly representative of the planning practices of that era, are then compared with their contemporary counterparts and subsequently with samples of their physical impacts on the ground, based on a morphological analysis of settlements and productive spaces in urban and rural contexts. Finally, we identify key changes for better use of productive soils within the Lisbon Region, considering challenges posed by international and national agendas.